Valorization of recycled aggregates to eco-efficient lightweight self-compacting mortars: Studies on microstructure, mechanical, durability, environmental, and economic properties - Ulas, Merve Acikgenc; Culcu, Muezeyyen Busra; Ulucan, Muhammed (Elsevier Sci Ltd, 2024)
This study focuses on a holistic approach to investigate the microstructural, mechanical, durability, environmental, and economic properties of lightweight self-compacting mortars (LWSCM) produced using different aggregate types (natural, recycled, lightweight) and supplementary cementitious materials (SCM). Within the scope of this study, 22 different LWSCM series were designed, 4 of which were reference, and silica fume (SF) and fly ash (FA) were used as SCM. Compressive and flexural tests were performed for mechanical tests at 7, 28, and 180 days. Significant improvements in flexural and compressive strengths were observed for 10% SF and 15% FA substitution. Total water absorption, capillarity, porosity, density, and sulfate resistance tests were carried out to investigate the durability properties. All mortar series exposed to sulfate solution significantly reduced flexural and compressive strength. Among the sulfate-exposed specimens, the mortar series containing 10% SF showed the most considerable flexural and compressive strength reductions. The global warming potential (GWP), waste generation (WG), and energy consumption (EC) were considered to evaluate environmental properties. Significant reductions in GWP and EC values were observed for mortar series with 30% SCM. Similarly, significant decreases in WG values were obtained with the increased use of recycled aggregate and SCM. Scanning electron microscope analyses were performed to examine the microstructural properties and detailed evaluations were made. Significant gains were achieved in economic properties due to the use of SCM, with total costs decreasing by approximately 10%, especially in series with 30% SCM. Considering the thousands of buildings constructed after the earthquake, sustainable development, and circular economy goals, using recycled aggregates and SCM to reduce the consumption of natural aggregates and cement has made significant contributions by making holistic evaluations.
Keywords: Lightweight self -compacting mortar; Construction and demolition waste; Sustainable development; Circular economy